Forming a sense of respect for the students in primary school educational lessons - Dilova Nargiza Gaybullayevna; Hakimova Nargiza Supxonovna (Zien Journals, 2022)
The article deals with social and legal norms, their role and significance in the development of society, to give primary school students an idea of social and legal norms, to form in their minds the competence to comply with these norms
Keywords: social and legal norms; competencies; life skills; quality of education